Memberi Perspektif pada Ilmu Komunikasi - Abrar, Ana Nadhya (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2002)
This article aim to describle some fields in communication studies. The fields are characterized by process of borrowing from other sciences and combining with the domain of communication studies. What is quite remarkable from this borrowwing and combination is that it creates some subdomains of communication studies, such as: development communication, political communication, environmental communication, and communication policy. These sub-domains ofcommunication studies tend to be practical, focusing on practicality rather than concepts. The impact of this on commnunication scholars is an issue that the scholars should have enough knowledge on empirical practice before or while studying the sub-domains of communication studies.